Quantitative Strategic Planning Matrix Dalam Penentuan Strategi Tata Kelola Air Sebagai Implementasi Green Campus Di Kampus UKSW - Cahyaningrum, Desti Christian (Program Studi Magister Manajemen Lingkungan, 2024)
Conservation, recycling, and saving of water are kinds of green campus implementation that necessary in daily basis on campus life. This is because of water consumption in the campus environment is quite large and has the potential to cause degradation of water resources. This research aims to analyze internal and external factors that can support or hinder the implementation of a green campus at UKSW based at the water management criteria in the UI GreenMetric. Resullts of external and internal factor identification then used for arranged water management strategies using the Quantitative Strategic Planning Matric (QSPM) approach. The result show that the current position of UKSW water management is still in the